Revenue Administration Reforms in anglophone Africa Since the Early 1990's - Kloeden, David (IMF Working Papers; Working Paper ;, 2011)
Despite positive but mixed progress over two decades, most lower income African countries need to enhance their low tax-to-GDP ratios by mobilizing domestic resources to complement debt relief, donor aid and to achieve the MDG and poverty reduction objectives. With these goals in mind, most African countries have undertaken revenue administration reforms and from the early 1990s, 16 of 19 Anglophone Africa countries established some form of revenue authority (RA) for greater governance, financing, and workforce autonomy. Changes in governance and HR practices are evident, but has revenue administration improved overall? Capacity limitations and integrity issues persist. The introduction of VAT heralded self-assessment, but in most instances without being integrated with income tax administration. Rather, VAT administration was assigned to a separate department. Special units for large taxpayers are now common following initial challenges, but programs for other taxpayer segments are still emerging.